Urban block configuration and the impact on energy consumption: A case study of sinuous morphology. (July 2022) - Shareef, Sundus; Altan, Hasim
Abstract: Building morphology and urban block configuration are influential urban design elements that control and optimize the outdoor and indoor thermal performance. In hot climate areas, cooling load is the major contribution to the total energy consumption, so it is essential to adopt design tools to enhance the building performance and reduce energy consumption and emissions. Previous studies proved the impact of urban block morphology on indoor energy consumption. However, the performance of buildings in Sinuous Configuration (SC) within the urban block has not been investigated in previous literature. This study aims to find the impact of SC of urban block configuration on outdoor microclimate parameters and indoor energy consumption. The UAE climate hot conditions were adopted to explore the SC of the urban block on outdoor thermal performance and indoor energy consumption using two simulation programs ENVI-MET and IES-VE. The outdoor thermal performance in this study is expressed by; 1) air temperature, 2) wind velocity, and 3) relative humidity at the height of the pedestrian level, 1.4 m from the ground. The results show that the SC where the buildings are arranged alternatively within the urban block, reduced the air temperature by 1.9 °C compared to the base case of grid arrangement. This result was reflected positively on energy consumption by reducing the conduction and solar gains, consequently, the cooling load decreased by 4.9% compared to the base case. Furthermore, the SC has a clear impact on wind speed and behavior, as wind speed reduced up to 68%, but the airflow and distribution enhanced within the urban block canyons and alleys around the buildings. This study contributes to urban planning policies and regulations by providing an optimized urban block configuration for hot climate areas. However, the impact of SC on outdoor thermal comfort in hot and humid areas can be recommended for further studies. Highlights: Studied the impact of sinuous configuration of urban block configuration on outdoor microclimate parameters and indoor energy consumption. The sinuous configuration where the buildings arranged alternatively within the urban block, reduced the air temperature by 1.9°C. Reducing the conduction and solar gains, consequently, the cooling load decreased by 4.9%. The sinuous configuration has a clear impact on wind speed and behavior; wind speed reduced up to 68%. It contributes to urban planning policies and regulations with an optimized urban block configuration for hot climate areas.